Self-Regulated Learning for New Tertiary Students in the Bachelor of Psychology Degree Course - Gianto Raymond Hia; Miryam Wedyaswari; Sarah Aurelia Saragih (ANIMA Indonesian Psychological Journal, 2018)
The transition from senior high-school to university is an important phase for new tertiary students to which they must adapt, particularly in academic matters. This study was conducted with new students (n = 95), commencing studies in 2017 at the Faculty of Psychology, Universitas Padjadjaran, Bandung, West Java, to obtain a picture of their abilities in self-regulated learning. The Bachelor of Psychology course, which is a Science subject, involves a great deal of social science, and so requires a unique study strategy, to enable new students to adapt in the academic field. This study utilized the Motivation Strategy Learning Questionnaire (MSLQ) measurement instrument scale, supplemented by a survey questionnaire regarding academic results. Some 70% of new tertiary students in the Bachelor of Psychology (BPsych) course organized their goals and regulated their motivation internally (internal goal motivation). The study strategy most used to regulate their cognition was elaboration, whilst there still tended to be a few who capitalized upon peer learning and critical thinking strategies in their learning processes (40%). The aspects of effort regulation and help seeking were found to be able somewhat to predict their Student Achievement Index (Indeks Prestasi Siswa–IPS). For this reason, the learning environment needs to be conditioned so that these two aspects are facilitated optimally.